(untitled) (Olhar de Professor, 2020)
We live in a neoliberal capitalist system that defends individualism and competition and where human actions are guided by the ideology of the free market. To overcome this oppressive and exploitative logic, I propose a dialogue between socialist feminism and a pedagogy of oppressed women as a collective and cooperative alternative, forged with and not for women. The objective of this theoretical investigation is to extend Paulo Freire’s theory to incorporate socialist feminism and, thus, build popular feminist and socialist education. To build a new world, massive protests, but also popular, socialist and feminist education work with small groups has become increasingly urgent in times of neoliberalism, such as the practices developed in Brazil, Canada, the United States and Bolivia. It is by reading the world, that is, knowledge created socially, and reading the word, systematized knowledge, that women can become critical of their context and fight for revolutionary social justice.